Polymer materials for prevention of postoperative adhesion. (1st October 2017) - Li, Jiannan; Feng, Xiangru; Liu, Baichun; Yu, Yingjie; Sun, Leming; Liu, Tongjun; Wang, Yongheng; Ding, Jianxun; Chen, Xuesi
Graphical abstract: Abstract: Postoperative adhesion (POA) is a common complication that often occurs after a variety of surgeries, such as plastic surgery, repair operations of abdominal, pelvic, and tendon, and so forth. Moreover, POA leads to chronic abdominal pain, secondary infertility in women, intestinal obstruction, and other severe complications, which significantly reduce the life quality of patients. In order to prevent the formation of POA, a number of strategies have been developed, among which an emerging method is physical barriers consisting of polymer materials. This review highlights the most commonly used natural and synthetic polymer materials in anti-adhesion physical barriers. The specific features of polymer materials are analyzed and compared, and the possible prospect is also predicted. Statement of Significance: Postoperative adhesion (POA) is a serious complication accompanied with various surgeries. Polymer material-based physical barriers have attracted a large amount of attention in POA prevention. The polymer barriers can effectively avoid the formation of fibrous tissues among normal organs by reducing the interconnection of injured tissues. In this review, specific features of the natural and synthetic polymer materials for application in POA prevention were presented, and the possible prospects were predicted. All in all, our work can provide inspiration for researchers to choose proper polymer materials for preclinical and even clinical anti-adhesion studies.